AMBIGUITAS PERATURAN DAERAH KABUPATEN TANAH DATAR TENTANG PAJAK DAERAH PERSPEKTIF SIYASAH DUSTURIYAH - Hibatul Wafi; Elsy Renie (Institut Agama Islam Negeri Batusangkar, 2021)
The focus of the research is how ambiguity is in the Tanah Datar Regency Regional Regulation Number 1 of 2018 concerning the Second Amendment to the Tanah Datar Regency Regional Regulation Number 6 of 2011 concerning Regional Taxes. The purpose of this paper is to explain, analyze whether ambiguity occurs in article 43 paragraph 1, article 44 paragraph 1, article 65 paragraph 4 letter h ambiguity in the Tanah Datar Regency Regulation Number 6 of 2011 concerning Regional Taxes as Amended by the Regency Regional Regulation Tanah Datar Number 1 of 2018 concerning the Second Amendment to the Regional Regulation of Tanah Datar Regency Number 6 of 2011 concerning Regional Taxes and to find out how to review article 43 paragraph 1, article 44 paragraph 1, article 65 paragraph 4 letter h Regional Regulation of Tanah Datar Regency Number 6 of 2011 concerning Regional Taxes as Amended by Regional Regulation of Tanah Datar Regency Number 1 of 2018 concerning the Second Amendment to Regional Regulation of Tanah Datar Regency Number 6 of 2011 concerning Regional Taxes in the Perspective of Siyasah Dusturiyah on the Establishment of Good Legislations in the review of Siyasah Dusturiah.